PENGARUH LOGAM Li PADA ADSORPSI ATOM-ATOM H OLEH PERMUKAAN GRAFENA PLANAR - Kusuma, Theresia Sita; -, Emdeniz; Arief, Syukri (Jurnal Riset Kimia, 2007)
ABSTRACT Graphene has future prospect for electronics. By adding some substituents this material can be tuned to behave like a metal or semiconductor. In this investigation, a planar single layer of modified graphene, C24H12-mLim (m = 0, 3, 6, and 12) consisted of seven six-member rings was used to adsorb the oncoming hydrogen (perpendicular to the surface, was defined as Had). A planar twolayer graphene C48H24 (7+7) was also included. To determine the adsorption models and the Had couverage, a semiempiris Calzaferri program, works on pentium 4 windows 98, was used to optimize nHad (n = 1, 2, and 3) that reached the surfaces. The heat of Had adsorption and the band gap of the surfaces were also computed. Results of these computations showed that: (1) the adsorption process was endothermic and Li reduced the heat of Had adsorption on the surfaces. (2) Li reduced the band gap of the surfaces, so C24H12 was a semiconductor but C24Li12 a conductor. (3) The adsorbed nHad always lowered the band gap of the surfaces, in exception of C24Li12 could be lower or higher. (4) Each atom on the surfaces, in exception hydrogen, might adsorb nHad formed tilted (with C) and lying down (with Li) surface complexes, and for C24H6Li6 an asymmetric twofold complex was also observed. (5) However, the Had couverage was low, some Had formed H2 and this was not observed on C24H6Li6. (6) The C48H24 kept an H2 molecule between layers. Thus, a new material C24H6Li6 which had two adsorption models, might increase the Had couverage, but had lower conductivity than that of C24H12. On the other hand, it is necessary to study in more details the hydrogen storage between graphene layers.        Key words: graphene, adsorption, substituent